Burial Ages Imply Miocene Uplift of Lu Mountain in East China due to Crustal Shortening - Han, Zhiyong; Pan, Rouxian; Li, Xusheng; Liu, Yujia; Li, Yufang; Wang, Xianyan (Frontiers in Earth Science, 2021)
Confined by the eastern and western boundary faults, Lu Mountain has long been considered a block mountain uplifted due to Mesozoic and Cenozoic crustal deformation in East China. However, the formation and evolution of this block mountain are still debated. In this study, the eastern boundary fault is investigated to confirm the tectonic style of the block mountain. In addition, the burial ages of sediments on the fans of the eastern piedmont are measured by 26Al/10Be dating to evaluate the denudation rate. Field evidence indicates the presence of a reverse fault (Xingzi reverse fault) acting as the eastern boundary fault, which demonstrates that the block mountain is not a horst as once thought but an extrusion structure. Corrected 26Al/10Be burial ages show that the sediments on the high-level fans were deposited at approximately 1.1-1.2 Ma, which indicates denudation rates ranging from 0.033 m/kyr to 0.082 m/kyr. The vertical displacement along the Xingzi reverse fault is estimated to be at least 1100 m. The hanging wall could have been eroded to its present position within 13-33 Myr at the above denudation rates. Combining our results with regional geological and geomorphological evidence, we suggest that Lu Mountain was mainly uplifted in the Miocene due to crustal compression deformation, which may have been a response to the movement of the Pacific plate.